Need Analysis on Teaching Media to Improve Morphological Awareness on Vocational Higher Students - Devi Kurniasari Riyadi (Fakultas Ilmu Budaya, Universitas Brawijaya, 2019)
Morphological awareness (MA) has relation to the language development. By having MA, it can be strong predictor in vocabulary and reading comprehension. Students of Politeknik Kota Malang was still lack of MA. It is because morphology study was not taught explicitly and there was not sufficient material. This study is aimed to investigate the students’ needs on developing teaching media to improve students’ morphological awareness (MA) that suits with their characters. From the result, they need teaching media in the form of game on ICT-based and the activity in the game can be expected for them to enrich the vocabulary and know the meaning of words. The game is also expected to provide them with a lot of texts and to help students in pronouncing the words correctly.